Marketing costs, margins and efficiency of domestic marine fish marketing in Kerala - Aswathy, N.; Narayanakumar, R.; Harshan, N. K. (Indian Journal of Fisheries, 2014)
Kerala is one of the important marine fish producing and consuming state in India. The total quantity of marine fish produced in the state increased from 6.04 lakh t in 2000 to 8.69 lakh t in 2012.The increase in the catches were mainly contributed by oilsardine and other low value pelagics while there was a decline in the catches of high value fishes. The reduction in the catches of high value fishes, rising costs of fishing and increased demand for marine fish in the domestic and export markets pushed up the prices. The prices of seer fishes, pomfrets and mackerels increased considerably at the retail markets in the state. This has promoted the increased transport of fish from other coastal states which involves more intermediaries in the marketing activity. The present paper discusses the structure of marine fish marketing in the state as well as the efficiency in different marketing channels. The analysis revealed that the marketing efficiency was high for commercial species like seerfishes where intermediaries were grabbing a significant share of the consumer’s rupee.